Corporate Donations to the Arts: Philanthropy or Advertising? - Björn Frank; Kurt Geppert (Deutsches Institut für Wirtschaftsforschung (DIW), 2002)
This paper is an attempt to provide evidence on two questions: Why do companies sponsor art events, and where exactly does the money go? We analyse data collected on the revenue structure of cultural institutions in Berlin and Hamburg. This data set not only tells us where the money goes, it also allows us to draw conclusions with respect to donors' motives. We regress sponsorships received on the number of visitors and other independent variables. The results are significantly different from those which one would expect if sponsoring were merely a form of advertising.
Keywords: Z1; C24; H4; 330; Sponsoring; Kulturfinanzierung; Unternehmen; Werbung; Altruismus; Schätzung; Deutschland